Thermal analysis on hydroxyapatite synthesis through mechanochemical method - Iis, Sopyan (Springerlink, 2011)
Thermal analysis of hydroxyapatite formation through dry mechanochemical method has been studied. The calcium phosphate was synthesized using calcium hydroxide and di-ammonium hydrogen phosphate as the precursors. The ball milling of 1/6 ball-powder mass ratio was employed on mixtures of calcium hydroxide and di-ammonium hydrogen phosphate in three different speeds 170, 270 and 370 rpm for 15 h. As ball-milled powders were then sintered at 1150, 1250 and 1350oC for 2 h, then subjected to TGA, XRD and FTIR for phase characterization. Calcium phosphates with ammonium are phases of the material. The ammonium is trace of phosphorus precursor. Choosing condition of the process and type of precursors determines type of reactions and its products.